The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acsomega.9b03755
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Silicon Photocatalyst for High-Efficiency Photocatalytic Water Splitting

Abstract: Metallurgical silicon was studied for photocatalytic H2 evolution activity. It has been found that metallurgical silicon with large particle size (above 800 nm) possesses poor photocatalytic activity because of the deteriorating photoelectric performance of the low-purity silicon. After size reduction (around 400 nm) and metal nanoparticle decoration, the photocatalytic performance was significantly enhanced to 1003.3 μmol·g–1·h–1. However, the photocatalytic performance of the Cu-, Ag-, and Pt-decorated silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Because SiNWs have a high capacity for “light absorption”, [ 7 ] high specific surface area, and higher bandgap than bulk silicon, [ 7,8 ] they meet the requirement for water splitting (to split the water molecule, 1.23 eV energy is necessary). [ 9–11 ] Despite this, there are few reports on SiNWs as a photocatalyst for direct hydrogen generation. [ 5,12–16 ] Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Because SiNWs have a high capacity for “light absorption”, [ 7 ] high specific surface area, and higher bandgap than bulk silicon, [ 7,8 ] they meet the requirement for water splitting (to split the water molecule, 1.23 eV energy is necessary). [ 9–11 ] Despite this, there are few reports on SiNWs as a photocatalyst for direct hydrogen generation. [ 5,12–16 ] Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, Ru-modified SiNWs as electrocatalysts for hydrogen evolution reaction exhibited higher performance in comparison to the pure Ru particles. Lv et al reported that after size reduction of metallurgical silicon (particle size around 400 nm) and metal nanoparticle decoration the photocatalytic performance was significantly enhanced up to 1000 μmol·g –1 ·h –1 . Hence, the decoration of SiNWs with AgNPs is a possible way to enhance the light absorption in the visible spectral range and hydrogen generation rate.…”
Section: Introductionmentioning
confidence: 99%
“…Lv et al reported that after size reduction of metallurgical silicon (particle size around 400 nm) and metal nanoparticle decoration the photocatalytic performance was significantly enhanced up to 1000 μmol•g −1 •h −1 . 19 Hence, the decoration of SiNWs with AgNPs is a possible way to enhance the light absorption in the visible spectral range and hydrogen generation rate. In this paper, three simple top-down wet-chemical-modified SiNWs with different AgNPs from electroless silver deposition (ELD), 20 silver mirror reaction (MR), 21 and native Ag particles have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…1 Silicon has established itself as one of the major semiconducting materials thanks to its high structural quality with suitable electronic properties such as band gap (1.12 eV), mobility, capability to be n or p doped and passivated by forming an insulating SiO 2 layer. Silicon also holds high interest in photonics 2 as a photodetector and light emitter, photocatalysis, 3 and solar cell applications. 4 Silicon based solar cells with an efficiency up to 26.7% represented about 95% of the worldwide production in 2020.…”
Section: Introductionmentioning
confidence: 99%